Tropical cyclone activities in the western North Pacific in 2023 - Xin Huang; Johnny C.L. Chan; Lina Bai; Zifeng Yu; Tingting Sun (Tropical Cyclone Research and Review)
Using the best-track dataset from the Shanghai Typhoon Institute/China Meteorological Administration, the paper presents a detailed summary and analysis of tropical cyclone (TC) activities in the Western North Pacific (WNP) and the South China Sea (SCS) during 2023. Based on historical records from 1951 to 2020 as the climatology benchmark, we examine anomalies in TC frequency, origin locations, tracks, intensity, and duration, as well as landfall events across the Asia-Pacific region. TC frequency in 2023 is found to be lower than climatology, with a marked decrease during the autumn months. Origin locations of TCs, which mark the starting points of their paths, are generally consistent with climatology, although there is a noticeable northwestward shift in the origins of the intense TCs. Track density of named TCs is anomalously high within the 0–20°N and 110°E to 125°E longitude box, and offshore areas covering northwestern to southern Japan and around the Korean Peninsula. Comparisons of the means, medians, upper and lower quartiles all indicate that TC intensity is generally stronger than usual, with 8 out of 17 named TCs reaching super typhoon status. The duration of TCs maintaining tropical storm intensity or above also surpasses climatological norms. In terms of landfall, 6 TCs made landfall in China, totaling 11 events, while 11 TCs accounted for 20 landfall instances across the Asia-Pacific. The key anomalous annual TC activities are influenced by atmospheric and oceanic conditions modulated by a concurrent El Niño event, a positive North Pacific Mode, a negative Pacific Meridional Mode on the interannual scale, and the negative Pacific Decadal Oscillation phase and positive Atlantic Multidecadal Oscillation phase on the interdecadal scale.